Was Federation Uniting or Dividing? The Impact of the Customs Union of 1901 on Australian Trade Relationships1. Issue 3 (26th July 2018) - Coleman, William
Abstract : The paper examines data on intra‐Australian trade and Australian international trade before and after the establishment of an Australian Customs union at Federation in 1901. The paper infers from these data that the Federation customs union cannot be simply summarised as 'nationalising' of Australian trade relationships. Internal trade ties did not unambiguously strengthen outside of Victoria. And while there is evidence that Victoria and New South Wales did redirect exports from the rest of the world to the rest of Australia, the data also indicate that the smaller states actually strengthened their exports to the rest of the world, perhaps as a resort in the face of a customs union that was a benefit to the larger states and not themselves.